Candida rugosa , an Emerging Fungal Pathogen with Resistance to Azoles: Geographic and Temporal Trends from the ARTEMIS DISK Antifungal Surveillance Program - (:unkn) unknown (My University, 2006)
ABSTRACT Candida rugosa is a fungus that appears to be emerging as a cause of infection in some geographic regions. We utilized the extensive database of the ARTEMIS DISK Antifungal Surveillance Program to describe the geographic and temporal trends in the isolation of C. rugosa from clinical specimens and the in vitro susceptibilities of 452 isolates to fluconazole and voriconazole. C. rugosa accounted for 0.4% of 134,715 isolates of Candida , and the frequency of isolation increased from 0.03% to 0.4% over the 6.5-year study period (1997 to 2003). C. rugosa was most common in the Latin American region (2.7% versus 0.1 to 0.4%). Decreased susceptibility to fluconazole (40.5% susceptible) was observed in all geographic regions; however, isolates from Europe and North America were much more susceptible (97 to 100%) to voriconazole than those from other geographic regions (55.8 to 58.8%). C. rugosa was most often isolated from blood and urine in patients hospitalized at the Medical and Surgical inpatient services. Notably, bloodstream isolates were the least susceptible to both fluconazole and voriconazole. C. rugosa should be considered, along with the established pathogens Candida krusei and Candida glabrata , as a species of Candida with reduced susceptibility to the azole antifungal agents.
Candida rugosa , an Emerging Fungal Pathogen with Resistance to Azoles